Luminescence Properties of Silicate Mineral: Charoite - KHANLARY*†, M.; TOWNSEND, P. (Asian Journal of Chemistry, 2009)
Luminescence measurements of charoite are reported which include two main emission bands centred near 380 and 600 nm. There are minor differences in response between cathodoluminescence and radioluminescence and greater differences between light and dark coloured charoite. For a dark sample, there is an additional band near 820 nm which has a discontinuity in intensity near 170 ºC. This feature is ascribed to loss of water bonded into the structure. Models for the emission bands in this gem stone are consistent with earlier proposals.